Role of norovirus in acute gastroenteritis in the Northwest of Spain during 2010–2011. Issue 11 (12th July 2013) - Manso, Carmen F.; Torres, Eva; Bou, Germán; Romalde, Jesús L.
Abstract A total of 2, 643 samples from patients with gastroenteritis in Galicia (NW Spain) were tested for the presence of Norovirus (NoV). NoV genogroup GI was detected in 416 (15.7%) samples, while NoV genogroup GII was detected in 278 (10.5%) samples. Mixed infections of NoV GI and GII were observed in 53 (2%) samples. Total prevalence of NoV in the analyzed samples was 28.3%. Besides NoV diagnosis assay, all the specimens were also submitted to routine clinical bacteriology tests. Cryptosporidium spp. as well as adenovirus (AdV) and rotavirus (RV) were determined on some samples after specific request by hospital units. The results obtained allowed to determine the disease etiology in 14.4% of the patients. Taking into account all the microorganisms studied, the etiological agent was determined for 39.5% of the cases. The results indicated that NoVs are the leading cause of acute gastroenteritis in all age‐groups in Northwestern Spain, and that the lack of routine NoV diagnosis contributes to the underestimation of the importance of this virus, not only in outbreaks, but also in sporadic cases of acute gastroenteritis. J Med. Virol. 85:2009–2015, 2013.. © 2013 Wiley Periodicals, Inc.